Achievement motivation, internal locus of control, goal orientation, and academic self-efficacy as outcome measures for a course designed to positively affect student academic performance. - Graham, Gina Marie. (My University, 2007)
This study attempted to expand our understanding of possible psychosocial predictive measures of student success and the effectiveness psychosocial outcome measures of an intervention course designed to assist at-risk students in becoming academically successful. Participants were from a large, southwest university and included traditional college age students who had been placed on academic probation by the university the previous semester. Based on Bandura's (1997) social cognitive theory, Deci and Ryan's (1991) self-determination theory and Tinto's (1975) model of student persistence, the study first compared pre- and post-test measures of achievement motivation, internal locus of control, academic self-efficacy, goal orientation, and academic and social integration. Paired-samples t-tests were used to analyze the data. The study also analyzed these measures for their predictive value of successful course and semester completion, using both logistical and multiple regression analyses. Outcomes were considered for program development and enhancement.
Keywords: Academic achievement.; Education, Educational Psychology.; College dropouts Prevention.